Scattering of X-rays during melting and solidification of thermoplastic polyurethane. Graphite as nucleating agent and stabilizer of the colloidal melt. (26th September 2018) - Stribeck, Almut; Dabbous, Raphaël; Eling, Berend; Pöselt, Elmar; Malfois, Marc; Schander, Edgar
Abstract: Melting and solidification of thermoplastic polyurethanes (TPU) are monitored by X-ray scattering. The colloidal character of the typical material becomes unstable as soon as the hard domains (HD) are molten. Then the scattered intensity fluctuates considerably and "lost" photons are found at small scattering angles (Tyndall effect). In this temperature regime the material is a fluid. Competing homogenization and segregation processes appear to take place, which modulate the materials colloidal character. Monitored by SAXS and WAXS, TPU elastomers are melted and re-solidified (heating rate: 20 K/min, temperatures T m a x : 220 °C, 190 °C). Strong fluctuations in scattering intensity due to varying Tyndall effect are observed in most of our experiments. Here the typical effects are demonstrated on a polyether-based TPU with a hard segment content of 30%, whose colloidal melt is stabilized by adding 0.5% graphite. In the hot quiescent melt the morphology is characterized by density undulations. HD arrangement does not grow late. Graphite stabilizes the colloidal melt. It increases both the HD melting-temperature (from 185 °C to 210 °C) and the HD formation temperature (from 90 °C to 165 °C). Graphical abstract: Image 1 Highlights: A TPU without hard domains appears as a heterogeneous colloidal fluid. Generally, temperature variation of the fluid induces mixing and demixing processes. There are indications that in the fluid even crystals may form. A nucleating agent may suppress mixing, demixing and crystallization. Graphite increases the temperatures of hard-domain melting and formation: increased thermal stability.